Regularities of the process of sulfation of the mixtures of organic substances - Dzevochko, Alyona; Podustov, Mykhaylo (Eastern-European Journal of Enterprise Technologies, 2016)
The main advantages and disadvantages of sulfatizing agents in the technology of obtaining surface active substances are presented. Characteristics of the apparatustechnological schemes of sulfating process of organic raw materials are given. The results are represented of research into the process of sulfation of the mixtures of organic substances by lowconcentrated gaseous sulphur trioxide in a volumetric reactor. Materials and methods of the research process are described. We experimentally found the ratio of higher alcohols of fraction С8–С10, higher alcohols of fraction С12–С14 and monoethanolamides of fatty acids of coconut oil (FA MEA) in the original mixture of organic raw materials. We demonstrate dependency of surface tension of aqueous solutions of SAS on the content of FA MEA. Dependencies of surface active substances quality on the main technological parameters are defined: molar ratio of the reagents, concentration of sulfur trioxide and temperature of the process of sulfation. It is demonstrated: at molar ratio of reagents 1.08:1, the maximum degree of sulfation is achieved with a slight increase in pastes chromaticity; the concentration of SO3 in the gas air flow must be maintained within 3.5–4.5 % by volume, the recommended temperature of the process is 318 K with a gradual decrease to 303 K. The data are presented on the change in magnitudes of density and viscosity of the reaction masses in the course of this process. Density of the reaction masses depends linearly on the degree of sulfation and decreases with increasing temperature. Dynamic viscosity of the reaction masses has an extremum at the degree of sulfation 70 % and a minimum at the degree of sulfation 85 %.